2015
DOI: 10.1371/journal.pntd.0003834
|View full text |Cite
|
Sign up to set email alerts
|

Airborne Transmission of Melioidosis to Humans from Environmental Aerosols Contaminated with B. pseudomallei

Abstract: Melioidosis results from an infection with the soil-borne pathogen Burkholderia pseudomallei, and cases of melioidosis usually cluster after rains or a typhoon. In an endemic area of Taiwan, B. pseudomallei is primarily geographically distributed in cropped fields in the northwest of this area, whereas melioidosis cases are distributed in a densely populated district in the southeast. We hypothesized that contaminated cropped fields generated aerosols contaminated with B. pseudomallei, which were carried by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
53
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 42 publications
1
53
1
Order By: Relevance
“…Skin inoculation is considered the main route of infection in agricultural workers in developing countries 14 . Recent evidence also suggests that inhalation of B. pseudomallei during extreme weather events 15,16 and ingestion of B. pseudomallei contaminated water are also important routes of infection 17 . High-risk groups include patients with diabetes mellitus, chronic kidney disease and excessive alcohol intake 12,18 .…”
mentioning
confidence: 99%
“…Skin inoculation is considered the main route of infection in agricultural workers in developing countries 14 . Recent evidence also suggests that inhalation of B. pseudomallei during extreme weather events 15,16 and ingestion of B. pseudomallei contaminated water are also important routes of infection 17 . High-risk groups include patients with diabetes mellitus, chronic kidney disease and excessive alcohol intake 12,18 .…”
mentioning
confidence: 99%
“…Recent work in Taiwan has shown that northwesterly winds during typhoon season were associated with melioidosis incidence and detection of B. pseudomallei-specific DNA in aerosols. 30 Water appears to serve as a vehicle to spread B. pseudomallei contamination. Interestingly, a study from Laos also noted an association between humidity and pediatric melioidosis cases, although the reasons for this are yet unclear.…”
Section: Climate Changementioning
confidence: 99%
“…Burkholderia pseudomallei infection may be acquired through inhalation, subcutaneous inoculation, or direct exposure of wounded skin to contaminated material. [10][11][12][13] Clinical presentations of melioidosis are highly variable, and can manifest as asymptomatic infection, localized skin abscesses, acute or chronic pneumonia, genitourinary, bone, and joint infections, or severe systemic sepsis with or without multiple abscesses in internal organs. Septic shock cases have a greater than 90% mortality rate.…”
Section: Introductionmentioning
confidence: 99%